2012
DOI: 10.1186/1471-2458-12-1057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water, sanitation, and hygiene practice and associated factors among people living with HIV/AIDS home based care services in Gondar city, Ethiopia

Abstract: BackgroundPeople living with HIV/AIDS have substantially greater need for water, sanitation, and hygiene. Encouraging hygiene education for People Living with HIV/AIDS in home based care services and additional support for the provision of water, sanitation, and hygiene services is recommended.MethodsA cross-sectional study was carried during 2009 to assess water, sanitation status and hygiene practices and associated factors among People Living with HIV/AIDS in home based care services in Gondar city of Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
1
26
2
Order By: Relevance
“…8,26 The observed significant association between educational attainment and sialorrhoea/anorexia, though cannot be easily explained, may not be unconnected with the general improvement in sanitation and hygiene practices that often attend higher levels of educational attainment. 27 The safety of drugs in pregnancy has been categorized by the United States Food and Drug into:…”
Section: Discussionmentioning
confidence: 99%
“…8,26 The observed significant association between educational attainment and sialorrhoea/anorexia, though cannot be easily explained, may not be unconnected with the general improvement in sanitation and hygiene practices that often attend higher levels of educational attainment. 27 The safety of drugs in pregnancy has been categorized by the United States Food and Drug into:…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge, attitudes, cost, and debilitating illness have all been noted as factors that inhibit access to or usage of improved WASH services and facilities by PLHIV. 21,22 Discrimination and social stigma have also limited access to WASH for PHLIV, who have reported being shunned from using certain water sources and sanitation facilities, and have had to travel further to access alternative water sources and sanitation facilities as a consequence. [22][23][24][25] Many studies have reported the health impact of WASH interventions among PLHIV [10][11][12][13][14][15][16][17][18][19][20] ; however, limited knowledge exists on WASH access and practices among HIV-positive individuals in rural Western Kenya where the rate of HIV among adults is high, about 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Unsafe and insufficient water, poor sanitation and hygiene are some of the factors contributing to poor health in low and middle-income countries (World Health Organization [WHO], community-based care, water is used to bath patients with HIV/AIDS, wash soiled clothing and linen, keep the home environment clean, take medication, cook food, and adopt hygienic practices to prevent the spread of infectious diseases (Yallew et al, 2012). Unfortunately, access to potable water, safe sanitation and good hygiene may become more difficult for people living with HIV/AIDS due to their declining physical health and worsening economic status (Yallew et al, 2012). A study conducted in Botswana found that 66% of caregivers indicated that water shortage undermined their daily activities (Ngwenya and Kgathi, 2006).…”
Section: Introductionmentioning
confidence: 99%